Pengaruh Perilaku Ibu Selama Kehamilan terhadap Status Kehamilan yang Tidak Diinginkan di Indonesia - Essi Guspaneza; Evi Martha (Media Kesehatan Masyarakat Indonesia, 2019)
Unwanted pregnancy status occurs because the mother have not ready to get pregnant and will theimpact on maternal behavior during pregnancy made mother tend to less doing the antenatal care visits, orprenatal care visits. This study aims to know the effect of maternal behavior during pregnancy towards unwantedpregnancy status. This study is a quantitative with using cross-sectional study design. The population is allpregnant women from 2017 IDHS survey in Indonesia of 1990 women, analyzed with univariate, bivariate andmultivariate. The results of the research showed women who having unwanted pregnancy of 12.8% and there arerelationship between maternal behavior during pregnancy (p=0.0001;OR=39,640) with unwanted pregnancy,after controlled age at pregnancy and parity. The probability of mothers who not doing ANC visit, parity >3and age at pregnancy <20 or >35 years having unwanted pregnancy status by 55%. Conclusion of this studyis that there are effect maternal behavior during pregnancy (ANC visits) towards unwanted pregnancy status.